(3QSGdI aj GdMjGA gd gh TQjYI Ch HOYIs - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg hMOg hHYO CjgG GdCHf GdeHGQc Sdc Gddg Hi hHc CMSf GdeSGdc (B_ (3Efc SCdJfi YeG hLOfG Ydjg BHGAfG ef Cf GdCHf dGjLJeY eY CHjg hUgQg hef ai eYfGge s
(3BNQgG (B:s
(3hCOfi GdfUjH efg GdJUOjb Hg hGdJSdje dCgdg hGddg SHMGfg hJYGdi CYde s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs